Nanotechnology in a nutshell : from simple to complex systems - Ngo, Christian; Voorde, M. H. van de (Marcel H.) (Berlin : Atlantis Press, 2014)
Provides an overview of nanotechnologies now and their applications in a broad variety of fields, including information and communication technologies, environmental sciences and engineering, societal life, and medicine, with provision of customized treatments.
Includes bibliographical references and index.
Keywords: Nanotechnology